Vancomycin in infusion during vitrectomy in surgical treatment of acute postoperative and posttraumatic endophthalmitis. Issue 1 (December 2016) - Rejdak, Robert; Choragiewicz, Tomasz; Kalinowska, Agnieszka; Koss, Michael; Ksiazek, Piotr; Moneta-Wielgos, Joanna; Maciejewski, Ryszard; Jünemann, Anselm; Nowomiejska, Katarzyna
Abstract Background Endophthalmitis is potentially devastating intraocular inflammation following eye trauma or surgery. We describe the visual outcomes and causative pathogens in acute bacterial postoperative and posttraumatic endophthalmitis treated with immediate pars plana vitrectomy (PPV) with Vancomycin dissolved in the infusion fluid. Methods Clinical records of consecutive 30 patients with postoperative endophthalmitis and 15 patients with posttraumatic endophthalmitis were evaluated. Vancomycin was administered constantly in the infusion fluid at the time of complete PPV. Cultures were prepared from anterior chamber paracentesis. The mean follow-up period was 13 months. Results The visual acuities were improved in 38 cases (84 %) and remained stable in seven cases (16 %). Median post-PPV visual acuity was 1.0 logMAR in a group with postoperative endophthalmitis and 1.3 logMAR in a group with posttraumatic endophthalmitis (p  < 0.05). Twenty cases (44 %) were culture-positive (Staphylococcus, Streptococcus, Enterococcus andBacillus spp ). Conclusions Early PPV with Vanomycin in infusion leads to vision improvement in patients with both posttraumatic and postoperative endophthalmitis. In our series of 45 cases culture was positive only in half of the cases.